Beyond uniformity: Enhancing students’ writing performance through differentiated instructions integrated with gallery photos - Siti Mafulah; Yeni Istayani; Umiati Jawas; Yulia Wahyuningsih (Universitas Muhammadiyah Malang, 2026)
In teaching Writing, usually teachers give the same instructions to all students, that caused the students’ low motivation and generic written output. Therefore, this study aims to explore the implementation of integration between differentiated Instructions (DI) and gallery photos (GP) on students' writing performance. Mixed methods used in this study with descriptive qualitative was used to find out how the implementation of integrated DI and GP as well as the teacher’s reflection, while to find out the effect on students’ writing, experimental design was used. This study was conducted in SMPN 1 Dampit, Indonesia, with 64 students of Eighth-grade students focused on recount text. The instruments used were tests, observation, interview, and the teacher’s journal reflection. Observation was done to find out how the implementation of the integration of DI and GP, and an interview was conducted with six students from different readiness groups. Besides, to see the significant effect of DI and GP on students’ writing performance, a t-test was calculated. The findings show that the integration of DI and GP effectively improve students’ writing performance and raise students’ engagement in the writing process. These findings can be applied to diverse students in a class that needs special treatment for each student without ignoring their proficiency levels, interests, and learning styles. It is suggested to future researchers to explore the effectiveness of this treatment to know further the effect of the integration of DI and Gallery Photo on different levels of the students.